Exploring the Roles of Cafes as Informal Learning Spaces Among College Students - Maria Teresa N. Bernabe; Ma. Crisandra C. Timbang; Alora Erica S. Salcedo; Ken Paul M. Espinosa (Future Science / FSH-PH Publications, 2026)
The increasing use of cafés by college students for academic activities highlights the need to examine their effectiveness as informal learning spaces. However, empirical evidence on how these environments support learning, performance, and student well-being remains limited. This study aimed to assess college students’ perceptions of cafes as informal learning spaces and determine how these venues are utilized for academic purposes. A descriptive–quantitative research design was employed, involving 100 college students who regularly studied in selected cafes in Baliwag City, Bulacan, Philippines. Data were collected using an expert-validated survey questionnaire and analyzed through descriptive statistical techniques. Findings revealed that students generally perceived cafes as conducive learning environments, particularly in terms of comfort (overall mean = 3.19) and accessibility (overall mean = 3.01). Physical amenities were also rated positively (overall mean = 2.86), although noise level received the lowest mean score (M = 2.51), indicating a key challenge. In terms of utilization, cafés supported self-directed learning (overall mean = 3.07) and positively influenced learning performance (overall mean = 3.06), with motivation emerging as the strongest factor (M = 3.12). Additionally, cafes contributed significantly to student well-being (overall mean = 3.18), especially in enhancing mood and motivation (M = 3.33) and reducing academic stress (M = 3.22). The study concludes that cafes function as effective informal learning spaces that promote motivation, independent learning, and well-being among college students. The findings offer practical implications for cafe owners and higher education institutions in developing more student-centered, supportive informal learning environments.